Invited: Towards Fully Intelligent Transportation through Infrastructure-Vehicle Cooperative Autonomous Driving: Challenges and Opportunities - Liu, Shaoshan; Yu, Bo; Tang, Jie; Zhu, Qi (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
The infrastructure-vehicle cooperative autonomous driving approach relies on the cooperation between intelligent roads and intelligent vehicles. This approach is not only safer but also more economical compared to the traditional on-vehicle-only autonomous driving. In this paper, we introduce the real-world deployment experiences of infrastructure-vehicle cooperative autonomous driving by PerceptIn, where a three-stage development roadmap is taken: infrastructure-augmented autonomous driving (IAAD), infrastructure-guided autonomous driving (IGAD), and infrastructure-planned autonomous driving (IPAD). We then discuss the future research challenges and opportunities for such approach.